2014
DOI: 10.1128/ec.00299-13
|View full text |Cite
|
Sign up to set email alerts
|

Endosymbiotic Gene Transfer in Tertiary Plastid-Containing Dinoflagellates

Abstract: Plastid establishment involves the transfer of endosymbiotic genes to the host nucleus, a process known as endosymbiotic gene transfer (EGT). Large amounts of EGT have been shown in several photosynthetic lineages but also in present-day plastid-lacking organisms, supporting the notion that endosymbiotic genes leave a substantial genetic footprint in the host nucleus. Yet the extent of this genetic relocation remains debated, largely because the long period that has passed since most plastids originated has er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 108 publications
6
61
0
Order By: Relevance
“…A similar picture can be drawn from a recent study of EGT in two tertiary plastid-bearing dinoflagellate lineages, the kareniaceans, which have a haptophyte-derived plastid, and the so-called "dinotoms," dinoflagellates with diatom plastids (88). A merit of the transcriptome-based datasets used in this analysis is that the tertiary acquisitions are relatively recent and the donor lineages (haptophytes and diatoms) are well defined, in principle making it easier to detect EGT against the dinoflagellate nuclear genomic background.…”
Section: The Fate Of Endosymbiotically Derived Nuclei and Their Genessupporting
confidence: 56%
“…A similar picture can be drawn from a recent study of EGT in two tertiary plastid-bearing dinoflagellate lineages, the kareniaceans, which have a haptophyte-derived plastid, and the so-called "dinotoms," dinoflagellates with diatom plastids (88). A merit of the transcriptome-based datasets used in this analysis is that the tertiary acquisitions are relatively recent and the donor lineages (haptophytes and diatoms) are well defined, in principle making it easier to detect EGT against the dinoflagellate nuclear genomic background.…”
Section: The Fate Of Endosymbiotically Derived Nuclei and Their Genessupporting
confidence: 56%
“…The dinoflagellates are the only eukaryotic lineage that has been shown to have undergone several plastid replacement events, where native plastids are replaced with those acquired from other algal groups [84]. Transcriptomic studies have played a key part in the relationships between photosynthetic and heterotrophic lineages of dinoflagellates, how organelles such as plastids have been gained and lost and have been vital for documenting gene transfer events between symbiont and host [86][87][88]. Further analysis of K. mikimotoi transcriptomic data revealed proof of events of independent plastid-to-host gene transfer in individual fucoxanthin plastid lineages acquired through tertiary endosymbiosis [87].…”
Section: Insight Into Dinoflagellates' Phylogeny and Evolutionmentioning
confidence: 99%
“…EST studies of fucoxanthin dinoflagellates have identified many gene transfers from the plastid to its host (70)(71)(72)(73). For example, in a recent study of the fucoxanthin dinoflagellates K. veneficum and Karenia brevis, Burki et al identified 90 ESTs of predicted haptophyte origin, including 34 that were predicted to encode a plastid targeting sequence, out of a total of 493 ESTs of definable phylogenetic affinity (74). Thus, ∼7% of the fucoxanthin dinoflagellate nuclear genome may encode proteins of haptophyte plastid origin, a figure approaching that found in other plastid lineages derived through secondary or tertiary endosymbiosis (9).…”
Section: Reductive Evolution Of Serially Acquired Dinoflagellate Plasmentioning
confidence: 99%
“…In the same study, the authors screened EST libraries of the dinotom algae K. foliaceum and D. baltica. Only 14 ESTs out of a total of 237 of definable phylogenetic origin resolved with diatoms, and none was predicted to encode a plastid-targeting sequence (74). The most recent study of gene transfer in Lepidodinium identified six ESTs, of probable green algal origin, that were predicted to contain a plastid-targeting sequence, from a total dataset of 4,746 sequences of both definable and uncertain phylogenetic origin (75).…”
Section: Reductive Evolution Of Serially Acquired Dinoflagellate Plasmentioning
confidence: 99%